Mengenal Imam Humaidi Dan Konsep Aqidahnya (Studi Komparatif Imam Humaidi Dan Imam Ibnu Abi Hatim) - M. Wahid Nur Tualeka (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACTBackground: Deviations in faith are a big disaster. How many damages occur due to irregularities in the issue of faith. A good faith will produce morals, because if someone has a good faith then his faith in Allah will be good while morality is a tsamrotuliman (the fruit of faith), then the goodness of one's faith will determine the goodness of one's morality. Because of the importance of this problem, the authors make a research with the title The concept of faith in the perspective of Imam Humaidi and Imam Ibnu Abi Hatim.Purpose of the study: To find out the comparison of the Islamic faith concept written by a great scholar of his time, Imam Humaidi and Imam Ibnu Abi HatimResearch methods: This research method is the library research method, which is research based on analyzes from sources in the form of books, articles, writings, and other library materials, and is carried out by documenting the words of Imam Humaidi and Imam Ibnu Abi Hatim related to the concept of both faiths.Research Results:That there are seven concepts of Imam Humaidifaith and no differences are found with the concept of faith which is owned by Imam Ibn Abi Hatim. In the sense that both have the same faith concept. The difference between the two is found in the country of origin of both, the number of works of each of the two, the difference of the Imam who became their respective teachers, the year of birth and death of both, and the attitude of the two towards Imam Bukhari in the matter of hadith.Keywords: Faith concept, Imam Humaidi, Imam Ibnu Abi Hatim